2023
DOI: 10.1002/cjoc.202200752
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Cracking of Polylactic Acid to Acrylic Acid

Abstract: Comprehensive Summary As a typical type of sustainable plastic, polyesters can be recycled or upcycled into value‐added chemicals in a variety of methods. However, excess reagents are required for most of the depolymerization and upcycling processes, causing the emission of environmental pollutants and the waste of chemical resources. Here we demonstrate a one‐pot catalytic process to directly crack polylactic acid into acrylic acid by acid catalyst with the assistance of an ionic liquid, Bu4PBr. Polylactic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…To this end, the chemical re/upcycling of biodegradable PLA plastics not only demonstrates technical feasibility but also holds significant scientific and practical value . Recently, Ma et al have demonstrated some interesting works on the topic, including converting waste PLA into alanine at 140 °C over Ru/TiO 2 catalyst using ammonia solution, transforming waste PLA into methyl propionate over the α-MoC catalyst in methanol solution at first and further reacting with formaldehyde to produce methyl methacrylate, and a one-pot catalytic process with Bu 4 PBr and an ionic liquid for the direct conversion of PLA into acrylic acid . This paper will furnish a comprehensive survey of the advancements achieved in the catalytic depolymerization of PLA polyesters.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To this end, the chemical re/upcycling of biodegradable PLA plastics not only demonstrates technical feasibility but also holds significant scientific and practical value . Recently, Ma et al have demonstrated some interesting works on the topic, including converting waste PLA into alanine at 140 °C over Ru/TiO 2 catalyst using ammonia solution, transforming waste PLA into methyl propionate over the α-MoC catalyst in methanol solution at first and further reacting with formaldehyde to produce methyl methacrylate, and a one-pot catalytic process with Bu 4 PBr and an ionic liquid for the direct conversion of PLA into acrylic acid . This paper will furnish a comprehensive survey of the advancements achieved in the catalytic depolymerization of PLA polyesters.…”
Section: Introductionmentioning
confidence: 99%
“… 23 Recently, Ma et al have demonstrated some interesting works on the topic, including converting waste PLA into alanine at 140 °C over Ru/TiO 2 catalyst using ammonia solution, 24 transforming waste PLA into methyl propionate over the α-MoC catalyst in methanol solution at first 25 and further reacting with formaldehyde to produce methyl methacrylate, and a one-pot catalytic process with Bu 4 PBr and an ionic liquid for the direct conversion of PLA into acrylic acid. 26 This paper will furnish a comprehensive survey of the advancements achieved in the catalytic depolymerization of PLA polyesters. Additionally, it will delineate the impediments encountered in realizing effective closed-loop recycling and upcycling processes.…”
Section: Introductionmentioning
confidence: 99%
“…18–23 Recently, more attention has been paid to waste as a resource on the basis of the unique properties of ionic liquids. 24–27 Nevertheless, there are few reports on the regeneration and reuse of waste acid in chemical reactions based on ionic liquids.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6] As a result, there is growing interest in the chemical recycling of CÀ O-linked plastics, both among researchers and in potential applications. [7][8][9] Many methods have been developed for the chemical recycling and upcycling of CÀ O-linked plastics, such as thermal degradation, hydrolysis, alcoholysis, hydrogenation, and hydrosilylation et al [10][11][12][13][14][15][16] Among these, alcoholysis is generally considered a more moderate method that doesn't require high temperature and pressure, inorganic strong acids or bases, or highly corrosive reagents. Additionally, alcoholysis is known for its better selectivity.…”
Section: Introductionmentioning
confidence: 99%